Toeplitz Operators on Abstract Hardy Spaces Built upon Banach Function Spaces - Karlovych, Oleksiy (2018)
This work was partially supported by the Fundacao para a Ciencia e a Tecnologia (Portuguese Foundation for Science and Technology) through the project UID/MAT/00297/2013 (Centro de Matematica e Aplicacoes).